Developing educational supervision in light of the quantitative and qualitative growth of educational supervisors and teachers in the city of Riyadh - Jarrah, Ali Yahya; Albaqih, Muhammad Nasser (Journal of Educational and Psychological Sciences, 2024)
This research aimed to assess the state of educational supervision in Riyadh, pinpoint challenges, and propose solutions for its enhancement. Employing a descriptive survey method, data was gathered via questionnaires from 339 participants representing various sectors. Results indicated a high level of reality and challenges in educational supervision, highlighting obstacles hindering its effectiveness. Proposed solutions emphasized streamlining and simplifying the role of educational supervisors. Recommendations included the separation of technical and administrative supervision, provision of adequate administrative support, creation of assistant supervisor roles, and the activation of professional learning communities. Additionally, suggestions were made to leverage electronic platforms for supervision, increase the number of supervisors, prioritize qualifications in appointments, and foster collective supervisory methods such as meetings and seminars. These recommendations aim to address current challenges and foster both quantitative and qualitative growth in educational supervision in Riyadh.
Keywords: educational supervision; quantitative growth; qualitative growth